Journalism across cultures - Cropp, Fritz; Cropp, Fritz; Frisby, Cynthia M.; Mills, Dean. (Ames : Iowa State Press, 2003)
Aimed at undergraduates in international or cross-cultural journalism courses, this book provides an overview of journalism issues across lines of race, culture, gender, age, sexual orientation, and ideology. It offers a report on an innovative approach to improved coverage of minorities through journalist and researcher collaboration.
Chapter 1, "Covering the Undercovered: The Evolution of Diversity in the News," Ronald B. Kelley and Dean Mills - - Chapter 2, "Women, Gender and the Media: A Look at Representation, Coverage and Workplace Issues," Jan Colbert -- Chapter 3, "A Problematic Press: Latinos and the News," Mercedes Lynn de Uriarte -- Chapter 4, "Media Coverage of Arabs and Arab Americans," Wesley G. Pippert -- Chapter 5, "The Changing Coverage of Gay, Lesbian, Bisexual and Transgendered Communities," Roy Aarons -- Chapter 6, "Just Don't Call 'EM 'Old Folks'," Kent S. Collins -- Chapter 7, "Taking the Mystery out of Native American Coverage," Teresa Trumbly Lamsam and Dennis McAuliffe Jr. -- Chapter 8, "Covering Religion," Judith M. Buddenbaum -- Chapter 9, "The Changing Faces of Advertising: Minority Images and the Media," Cynthia M. Frisby -- Chapter 10, "People with Disabilities," Elizabeth Wissner-Gross, with contributions by Alexander Wissner-Gross -- Chapter 11, "From a Troubled Past to a Confused Present: The Need for Better Coverage of Asian Americans," Fritz Cropp
Includes bibliographical references and index.
Keywords: Minorities -- Press coverage -- United States